Steinmetzite, Zn2Fe3+(PO4)2(OH)·3H2O, a new mineral formed from alteration of phosphophyllite at the Hagendorf Süd pegmatite, Bavaria. (1st April 2017) - Grey, I. E.; Keck, E.; Kampf, A. R.; Mumme, W. G.; Macrae, C. M.; Gable, R. W.; Glenn, A. M.; Davidson, C. J.
Steinmetzite, ideally Zn2Fe3+(PO4)2(OH)·3H2O, is a new mineral from the Hagendorf-Süd pegmatite, Hagendorf, Oberpfalz, Bavaria, Germany. Steinmetzite was found in a highly oxidized zone of the Cornelia mine at Hagendorf-Süd. It has formed by alteration of phosphophyllite, involving oxidation of the iron and some replacement of Zn by Fe. Steinmetzite lamellae co-exist with an amorphous Fe-rich phosphate in pseudomorphed phosphophyllite crystals. The lamellae are only a few μm thick and with maximum dimension ∼50 μm. The phosphophyllite pseudomorphs have a milky opaque appearance, often with a glazed yellow to orange weathering rind and with lengths ranging from sub-mm to 1 cm. Associated minerals are albite, apatite, chalcophanite, jahnsite, mitridatite, muscovite, quartz and wilhelmgümbelite. Goethite and cryptomelane are also abundant in the oxidized zone. The calculated density is 2.96 g cm–3. Steinmetzite is biaxial (–) with measured refractive indices α = 1.642(2), β = 1.659 (calc.), γ = 1.660(2) (white light). 2V(meas) = 27(1)°; orientation is Y ≈ b, X ^c ≈ 27°, with crystals flattened on {010} and elongated on [001]. Pleochroism shows shades of pale brown; Y > X ≈ Z. Electron microprobe analyses (average of seven crystals) with Fe reported as Fe2O3 and with H2O calculated from the structure gave ZnO 31.1, MnO 1.7, CaO 0.5, Fe2O3 21.9, Al2O3 0.3, P2O5 32.9, H2O 14.1 wt.%, total 102.5%. The empirical formula based on 2 P and 12 O, with all iron as ferric and OH– adjusted for charge balance is Zn1.65Fe3+1.19 Mn2+0.11Ca0.03Al3+0.02(PO4)2(OH)1.21·2.79H2O. The simplified formula is Zn2Fe3+(PO4)2(OH)·3H2O. Steinmetzite is triclinic, P1, with unit-cell parameters: a = 10.438(2), b = 5.102(1), c = 10.546(2) Å, α = 91.37(2), β = 115.93(2) and γ = 94.20(2)°. V = 502.7(3) Å3, Z = 2. The strongest lines in the powder X-ray diffraction pattern are [dobs in Å (I) (hkl)] 9.313(65) (100), 5.077(38) (010), 4.726(47) (002), 4.657(100) (200), 3.365 (55) (302), 3.071(54) (112) and 2.735(48) (312). The structure is related to that of phosphophyllite.